Evolution of morphology and microstructure of GaAs/GaSb nanowire heterostructures - Shi, Suixing (Nanoscale Res Lett, 2015)
In this paper, we successfully grow GaAs/GaSb core-shell heterostructure nanowires (NWs) by molecular beam epitaxy (MBE). The as-grown GaSb shell layer forms a wurtzite structure instead of the zinc blende structure that has been commonly reported. Meanwhile, a bulgy GaSb nanoplate also appears on top of GaAs/GaSb core-shell NWs and possesses a pure zinc blende phase. The growth mode for core-shell morphology and underlying mechanism for crystal phase selection of GaAs/GaSb nanowire heterostructures are discussed in detail.